Bacterial-derived nutrient and carbon source-sink behaviors in a sandy beach subterranean estuary. (November 2020) - Chen, Xiaogang; Ye, Qi; Sanders, Christian J.; Du, Jinzhou; Zhang, Jing
Abstract: Microbial communities in subterranean estuaries play important roles in the biogeochemical cycle. However, the microorganisms associated with biogeochemical behaviors in subterranean estuaries have received little attention. Here, the bacterial communities were compared between the fresh and saline groundwater in a subterranean estuary. Correlation analysis between bacterial groups and salinity indicated that different species represented different groundwater types. The key bacterial groups found along the subterranean estuaries have been shown to influence organic pollutant degradation and nitrate utilization. These species may be potential candidates for the in situ bioremediation of subterranean estuaries that are contaminated with pollutants. The utilization of nitrate and organic pollutants by bacteria in subterranean estuaries serves as a nitrate sink and inorganic carbon source. Our results show the role of bacteria in remediating pollutants through submarine groundwater discharge (SGD) to the coastal ocean, and specific species may be helpful in selecting reasonable groundwater end-members and reducing SGD uncertainties. Highlights: Significant differences in bacterial communities were found in fresh and saline submarine groundwater discharge (SGD). Bacterial processes contributed to the nitrate sink and dissolved inorganic carbon (DIC) behavior of the studied SGDs. Bacteria in submarine groundwater can reduce the amounts of nutrients entering the ocean via the SGD conduit. Key bacterial groups could be candidates for in situ bioremediation of polluted SGDs. Bacterial differences along subterranean estuaries can help in selecting appropriate groundwater end-members.